Tropical Diseases: Responses of pharmaceutical companies - Behrman, Jack N. (Washington, D.C.: American Enterprise Institute for Public Policy Research, 1980)
This book examines what the pharmaceutical companies have done in the past to combat the six most prevalent tropical diseases and what they are doing today, both within their own laboratories and in conjunction with health agencies in developing countries. The Brazilian program was examined at firsthand by the author, and the case study is based on interviews with officials of the government, observation of program activities in the field, and a review of documents provided by Brazilian officials.
Includes bibliographical footnotes.
ne 22/05/2018
Loans
Keywords: Tropical medicine; Pharmaceutical policy; Medical policy; Schistosomiasis- Brazil